Rare Metal Technology 2015 - Neelameggham, Neale; Alam, Shafiq; Oosterhof, Harald; Jha, Animesh; Dreisinger, David; Wang, Shijie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This collection presents the papers from a symposium on extraction of rare metals as well as rare extraction processing techniques used in metal production. Paper topics include the extraction and processing of elements like antimony, arsenic, calcium, chromium, hafnium, gold, indium, lithium, molybdenum, niobium, rare earth metals, rhenium, scandium, selenium, silver, strontium, tantalum, tellurium, tin, tungsten, vanadium, and zirconium. Rare processing techniques presented include bio leaching, molecular recognition technology, recovery of valuable components of commodity metals such as magnesium from laterite process wastes, titanium from ilmenites, and rare metals from wastes such as phosphors and LCD monitors.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering